Treatment of striae albae with 1,550 nm Er: Glass vs. CO2 fractional laser: A self-controlled study - Luo, Yanfei; Lin, Yan; Wang, Meiling; Gao, Xiaoyuan; Liu, Xiaodong; Liu, Huaxu (Frontiers in Medicine, 2023)
Objective The objective of this study was to compare the efficacy and safety of fractional CO2 laser and 1,550 nm Er: glass laser in the treatment for the patients with striae albae. Methods The female adults with striae albae in the abdomen for at least 12 months were recruited. After informed consent obtained, the patient received three treatments at 2-month intervals. The lesions on the left abdomen were treated with 10,600 nm CO2 fractional laser and right side treated with 1,550 nm Er: glass fractional laser. The pictures were taken before each visit and 3 months after the final treatment. The criteria for the evaluations using a quartile grading scale were excellent (76–100%), good (51–75%), fair (26–50%), poor (1-25%), and no improvement (0%). The safety and efficacy of the two lasers were independently evaluated using before and after photographs by two dermatologists. In addition, the self-reports to investigate the pain and satisfaction from patients were also recorded. Results Totally, 27 cases were recruited, and 25 patients completed the treatments and follow-up. The excellent and good results (improvement of 51–100%) were achieved on the right abdomen in 84% of the patients, while 48% on the left site (p < 0.05). Hyper-pigmentation was seen in 20% of the patients assessed on the left abdomen and only in 8% on the right abdomen. During the treatments, average score of the pain on the right abdomen was 5.41 ± 2.13, which was higher than that on the left (4.19 ± 2.12) (p < 0.001). No permanent hyper-pigmentation was found on the both sides. Considering the whole treatments, the patients favored the modality used on the right side (80 vs. 68%, p < 0.05). Conclusion Compared with CO2 fractional laser, 1,550 nm Er: glass fractional laser therapy provides the significantly better clinical outcomes and fewer side effects in the treatment of striae albae. Limitations The sample size and follow-up time were limited.